Multiple Research Methods as a Way to Explore the Longitudinal Impact of the Rural Village Library in Africa - Dent, Valeda F. (Qualitative and Quantitative Methods in Libraries, 2017)
This paper will focus on the body of qualitative and quantitative research conducted since 2004 to explore the impact of several rural libraries in Uganda and Burkina Faso, in Africa. This longitudinal study is ongoing, and outcomes are currently being used to support the development of a rural village library framework in Uganda, and perhaps elsewhere on the continent, as well as generate support for these village libraries in Africa. Areas being studied include impact of the libraries on student academic achievement, impact on teaching, impact on local literacy practices, impact on mother/child literacy practices, impact on learning readiness of young children, and impact on local economic development. Various approaches were used to gather data including psychological measures, focus groups, participant observation, ethnographic interviews, and questionnaires.